2016
DOI: 10.4238/gmr.15017850
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Impact of early enzyme-replacement therapy for mucopolysaccharidosis VI: results of a long-term follow-up of Brazilian siblings

Abstract: ABSTRACT. Mucopolysaccharidosis type VI (MPS VI)is an autosomal recessive multisystem lysosomal storage disorder, which is characterized by the deficiency of the enzyme arylsulfatase B encoded by the ARSB gene. Treatment of this disease with enzyme-replacement therapy (ERT) improves the clinical status of and generates hope for MPS VI patients. However, only few reports on patients with MPS VI treated before 5 years of age have been published. Thus, the objective of this study was to compare the clinical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Clinical trials show that ERT can improve quality of life and clinical and physical function, although eventually in the longterm, improvement reaches a plateau [20,21]. Overall, the current literature supports the safety and efficacy of ERT [22], especially when started at a young age [23][24][25][26].…”
Section: Introductionmentioning
confidence: 69%
“…Clinical trials show that ERT can improve quality of life and clinical and physical function, although eventually in the longterm, improvement reaches a plateau [20,21]. Overall, the current literature supports the safety and efficacy of ERT [22], especially when started at a young age [23][24][25][26].…”
Section: Introductionmentioning
confidence: 69%
“…Different evolution in the youngest siblings involved development of facial bones, joint stiffness, other skeletal deformities and growth, organomegaly and heart valves [79,80,[145][146][147][148][149]. In two families with MPS VI, joint mobility was preserved in the youngest sibling but progressive bone deformities and corneal clouding had developed also in the youngest sibling [176,177]. All together, these cases underline the importance of early treatment.…”
Section: Ert In Siblingsmentioning
confidence: 89%
“…A series of impressive clinical observations in siblings treated at different ages showed that ERT is reasonably able to modify the clinical course of the disease if administered at an early age [142,143,[176][177][178][179][180][181]. These case studies are only observations and not blind placebo-control studies, but they are relevant enough because they all go in the same direction.…”
Section: Ert In Siblingsmentioning
confidence: 99%
“…Table presents a summary on the effect of treatment for each outcome. The studies showed that the enzyme replacement therapy had a positive effect on the patient's survival outcomes (mortality), quality of life specific domains, lung function improvement, increased range of joint motion (joint mobility), physical resistance improvement, reduction of urinary GAG, and growth …”
Section: Clinical Outcomesmentioning
confidence: 99%